Methane production potential of feed ingredients estimated by in vitro gas production test - M.Ramachandran; A. Bharathidhasan; V.Balakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to investigate methane production potential of feed ingredients to develop a database on methane production. Feed ingredients such as cereal grains, cereal by-products and protein supplements were tested for methane production potential using in vitro gas production technique. In vitro true digestibility (IVTD) of cereal grains ranged from 60.1 to 96.7% and oats grain (76.2%) and distiller’s grain (60.1%) had lower (P<0.05) values than other cereal grains. Among the cereal by-products, wheat bran showed highest (P<0.05) IVTD (74.9%) than rice bran (42.7%). IVTD of cottonseed oil cake, black gram and sunflower oil cake was lower (P<0.05) than other protein supplements. Methane production potential of cereal grains at half life (t1/2) ranged from 0.66 to 2.85 ml/100 mg truly digested substrate and the difference was significant (P<0.05), however, maize grain, sorghum grain, bajra and broken rice did not vary among themselves. Average methane production potential of cereal by-products at half life (t1/2) and 24 hrs was 1.27 and 1.81 ml/100 mg truly digested substrate, respectively. Average methane production potential of protein supplements at half life (t1/2) and 24 hrs was 1.39 and 1.75ml/100 mg of truly digested substrate, respectively and the difference was statistically significant (P<0.05). Maximum (P<0.05) methane production potential at half life (t1/2) was recorded for black gram (4.07 ml/100 mg truly digested substrate). Lowest methane production potential both at half life (t1/2) and 24 hrs were recorded in fish meal and spirulina. It can be concluded that among cereal grains, methane production potential was higher (P<0.05) in oats grain at half life (t1/2) and all the cereal grains had similar methane production potential at 24 hrs. Among cereal by-products, wheat bran had higher (P<0.05) methane production potential both at half life (t1/2) and 24 hrs. Among protein supplements, black gram had significantly (P<0.05) higher methane production potential at half life (t1/2) and horse gram had significantly (P<0.05) higher methane production potential at 24 hrs.